The treatment efficacy of vitiligo patients attending in a dermatology clinic: an impact of clinico-epidemiological profiles and co-morbidities - Rahaman, Md Mahabubur; Asma, Anzirun Nahar; Siddiqua, Ayesha; Akter, Sabrina; Siddique, Rahmat Ullah; Alam, Morshad (Asian Journal of Medical and Biological Research, 2023)
There is widespread misinformation, taboos, and a lack of scientific analysis about vitiligo. In Bangladesh, there is a scarcity of research on vitiligo, though advanced treatments are widely available. This study aimed to investigate the treatment efficacy of vitiligo in a selected dermatology clinic and analyze the factors that impact the efficacy level. This was an analytical cross-sectional study among vitiligo patients who attended a dermatology clinic for treatment and were followed up for at least six months. Patients were treated by experienced physicians through a holistic treatment approach. An interviewer-administered questionnaire was used to collect information after obtaining informed consent. The data was processed by Microsoft Excel 2013 and analyzed by SPSS 25.0. The mean age of the study participants was 25.14 ± 13.32 years, where 60% were female. Acrofacial (33%), focal (27%), and acral (14%) are the most common types of vitiligo, and the face (n=73) is the most common body part. We have seen excellent treatment efficacy as proven by 94% of patients' lesion sizes decreased and 96% gained repigmentation at six months' follow-up. Our study revealed there is a negative impact of the presence of systemic disease and co-morbidities on vitiligo. The efficacy of the treatment was significantly affected by advanced age, body surface area, hypertension, diabetes, and anemia (P<0.05). Our analysis revealed a good treatment efficacy of holistic treatment for vitiligo in selected clinic. For more effective treatment, control of co-morbidities is essential. The findings of this study will help clinicians in their decision making during the treatment process of vitiligo. Asian J. Med. Biol. Res. 2023, 9 (2), 51-58